When strong ties are strong: Networks and youth labor market entry - Francis Kramarz; Oskar Nordström Skans (Institute for Labour Market Policy Evaluation (IFAU), 2011)
The conditions under which young workers find their first real post-graduation jobs are both very important for the young's future careers and insufficiently known given their public policy implications. To study these conditions, and in particular the role played by networks, we use a Swedish population-wide linked employer-employee data set of graduates from all levels of schooling which includes detailed information on family ties, neighborhoods, schools, and class composition over a period covering high as well as low unemployment years. We find that strong social ties (parents) are an important determinant of where young workers find their first job. This remarkably robust effect is estimated controlling for all confounding factors related to time, location, education, occupation, and the interaction of these. The effect is larger if the graduate's position is weak (low education) or during high unemployment years, a pattern which does not emerge when analyzing the role of weak ties (neighbors or friends as measured using classmates and their parents). On the hiring side, by contrast, the effects are larger if the parent's position is strong (e.g. by tenure or wage). We find no evidence of substitution in recruitment over time and fields induced by family ties hires. However, we do find that, just after their child is hired in their plant, parents experience a sharp drop in their wage growth. Overall, our results show that strong (family) ties are more important in the job finding process of young workers in weak positions than those weak ties usually measured in the literature (neighbors, in particular), suggesting that labor market experience and education are essential conditions for weak ties to be strong.
Keywords: J62; J64; J24; 330; Weak ties; social networks; youth employment; Junge Arbeitskräfte; Jugendliche; Arbeitsmarkt; Soziales Netzwerk; Schweden